A Morphemic Analysis of Sindhi, Dhatki, and Balochi Derivational and Inflectional Morphemes - Zahid Ali; Muhammad Shoaib Khan; Najamuddin Sohu; Muhammad Nadeem Jalbani (Kurdish Studies, 2024)
A morpheme is a smallest meaningful unit of a language (Yule, 1996; Carnie, 2006; Radford, 2009). A morpheme plays a vital role in the form and meaning of a sentence in general and words in particular. One morpheme can be generated from other morpheme; it can change its form and meaning. Derivational morphemes are used to alter the grammatical category of (e.g., education from educate, careful from care). Inflectional morphemes are used to show number (singular or plural), to show tense aspect (present, past, or future). Such morphemes are also used to alter the form of a word (e.g., older from old). The current study attempts to describe, analyse and compare derivational and inflectional morphemes in English, Sindhi and Balochi. The study answers the research question: How are English derivational and inflectional morphemes different from the Sindhi and Balochi ones? The theory of Morphemic Analysis (Haegeman, 1996; Carnie, 2006 & Radford, 2009) is applied to analyse the data of the three languages. This research work is primarily a qualitative in nature. It uses explanatory research design to analyse and compare the data of the above mentioned three languages. The data have been collected through interviews from the two native Sindhi and Balochi speakers. The participants are asked different questions about their personal and professional life so that they could speak more freely and naturally.